PENINGKATAN PEREKONOMIAN RAKYAT DI KARESIDENAN REMBANG MELALUI PENGELOLAAN TERNAK TAHUN 1900-1942 (SUATU KAJIAN HISTORIS) - Sarjanawati, Rr. Sri Wahyu (Faculty of Social Science, Universitas Negeri Semarang, 2010)
Ranch as one of the community in supporting the economy Residency Rembang has received attentionfrom the colonial government. It can be seen from one of the policies issued by the government at thattime, the effort to develop the farm. Government’s attention not only on livestock assistance, but alsoanimal health itself. It can be seen from the legislation, regulations or policies issued by the governmentrelating to the health of livestock. In this study the problems will be solved are: how the developmentof Animal Husbandry in Residency Rembang from 1900-1942, how the management of livestock inRembang Residency in 1900-1942, and how the government efforts in improving the health of livestockin Residency Rembang from 1900-1942? This research uses historical method. The fi nal stage is thepreparation or compilation of historical writing that is the facts in a synthesis as a unifi ed whole. Theresults showed that the growth of ranch increased Residency Rembang. The increase is not free fromgovernment interference. In the management of livestock can not be separated from the supervision andexamination by the Department of Livestock Health. This was done to improve the quality of livestock.Prevention of disease in cattle infectious anticipated by the government passed legislation preventinginfectious diseases and quarantine cattle.Key words: Livestock, livestock management, livestock health